Collected writings - Paine, Thomas 1737-1809 (New York : The Library of America, 1995)
Common sense, the crisis, and other pamphlets, articles, and letters.
Rights of man.
The age of reason.
Contenido : <Common sense, The crisis, and other pamphlets, articles, and letters> <Rights of man> <The age of reason>
Keywords: ESTADOS UNIDOS; LITERATURA AMERICANA USA; ESCRITOS; CARTAS; CAJA 3